Odpowiedź:
a)
[tex]a + b = 3 \times {10}^{9} + 1.5 \times {10}^{8} = 3 \times 10 \times {10}^{8} + 1.5 \times {10}^{8} = 30 \times {10}^{8} + 1.5 \times {10}^{8} = 31.5 \times {10}^{8} [/tex]
[tex]a - b = 3 \times {10}^{9} - 1.5 \times {10}^{8} = 30 \times {10}^{8} - 1.5 \times {10}^{8} = 28.5 \times {10}^{8} [/tex]
b)
[tex]a + b = 4.2 \times {10}^{ - 3} + 1.3 \times {10}^{ - 4} = 4.2 \times {10}^{ - 3 } + 1.3 \times {10}^{ - 1} \times {10}^{ - 3} = 4.2 \times {10}^{ - 3} + 0.13 \times {10}^{ - 3} = 4.33 \times {10}^{ - 3} [/tex]
[tex]a - b = 4.2 \times {10}^{ - 3} - 0.13 \times {10}^{ - 3} = 4.07 \times {10}^{ - 3} [/tex]
c)
[tex]a + b = 3.4 \times {10}^{15} + 7.1 \times {10}^{14} = 3.4 \times 10 \times {10}^{14} + 7.1 \times {10}^{14} = 34 \times {10}^{14} + 7.1 \times {10}^{14} = 41.1 \times {10}^{14} -[/tex]
[tex]a - b = 34 \times {10}^{14 } - 7.1 \times {10}^{14} = 26.9 \times {10}^{14} [/tex]